3D Heisenberg universality in the van der Waals antiferromagnet NiPS3 - Rajan Plumley; Sougata Mardanya; Cheng Peng; Johannes Nokelainen; Tadesse Assefa; Lingjia Shen; Nicholas Burdet; Zach Porter; Alexander Petsch; Aidan Israelski; Hongwei Chen; Jun-Sik Lee; et al. (npj Quantum Materials)
Abstract Van der Waals (vdW) magnetic materials are comprised of layers of atomically thin sheets, making them ideal platforms for studying magnetism at the two-dimensional (2D) limit. These materials are at the center of a host of novel types of experiments, however, there are notably few pathways to directly probe their magnetic structure. We confirm the magnetic order within a single crystal of NiPS3 and show it can be accessed with resonant elastic X-ray diffraction along the edge of the vdW planes in a carefully grown crystal by detecting structurally forbidden resonant magnetic X-ray scattering. We find the magnetic order parameter has a critical exponent of β ~ 0.36, indicating that the magnetism of these vdW crystals is more adequately characterized by the three-dimensional (3D) Heisenberg universality class. We verify these findings with first-principles density functional theory, Monte-Carlo simulations, and density matrix renormalization group calculations.